Brine shrimp cytotoxicity bioassay of red mangrove (Rhizophora mucronata) leaves using different solvents and its potency as antibacterial - ILHAM ZULFAHMI; EPA PAUJIAH; ZULTIRA HARINA ROZA; KAMALIAH HELMI; BADRATUN NAFIS; FIRMAN MUHAMMAD NUR; PUTROE NURUL FAZILA (Society for Indonesian Biodiversity, 2024)
Abstract. Zulfahmi I, Paujiah E, Roza ZH, Helmi K, Nafis B, Nur FM, Fazila PN. 2024. Brine shrimp cytotoxicity bioassay of red mangrove (Rhizophora mucronata) leaves using different solvents and its potency as antibacterial. Biodiversitas 25: 3227-3236. This study evaluates the cytotoxicity of ethanol, ethyl acetate, and n-hexane extracts of red mangrove (Rhizopora mucronata) leaves and their potential against pathogenic bacteria. Red mangrove leaf was evaluated for its cytotoxicity using the Brine Shrimp Lethality Test (BSLT). Each solvent's LC50 - 24-hour value was determined using probit analysis and measured using one-way ANOVA with a 95% confidence interval (P<0.05). The secondary metabolic compounds in each extract were presented and analyzed descriptively using GC-MS analysis. The effect of incubation time on the bacterial inhibition zone was tested using independent t-test analysis against S. aureus, V. parahaemolyticus, and A. hydrophyla. The results showed that the LC50 value of ethanol extract was 402.45 ppm, ethyl acetate extract was 230.97 ppm, and n-hexane extract was 180.31 ppm. The secondary metabolite compounds observed in red mangrove leaves extracted with different solvents (ethanol, ethyl acetate, and n-hexane) include terpenoids, alkaloids, ketones, phenols, turpentine oil, essential oils, unsaturated fats, and camphor. The ethyl acetate extract from red mangrove leaves inhibited the growth of S.aureus and V. parahaemolyticus. A. hydrophila and V. parahaemolyticus exhibited the lowest inhibition zone, which varied based on time and concentration.